Constructing 'Pakistan' through Knowledge Production in International Relations and Area Studies - Waheed, Ahmed W. author. aut Link
XVII, 230 p. 1 illus.
Keywords: This book analyses the discourse on Pakistan by exploring the knowledge production processes through which the International Relations community, Asian and South Asian area study centres, and think-tanks construct Pakistan’s identity. This book does not attempt to trace how Pakistan has been historically defined, explained, or understood by the International Relations interpretive communities or to supplant these understandings with the author’s version of what Pakistan is. Instead, this study focuses on investigating how the identity of Pakistan is fixed or stabilized via practices of the interpretive communities. In other words, this book attempts to address the following questions: How is the knowledge on Pakistan produced discursively? How is this knowledge represented in the writings on Pakistan? What are the conditions under which it is possible to make authoritative claims about Pakistan? Ahmed W. Waheed is an Assistant Professor at the Center for International Peace and Stability, National University of Sciences and Technology, Islamabad, Pakistan. He is the author of The Wrong Ally: Pakistan’s State Sovereignty under US Dependence (2018).